(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Comments on the results of cervical cancer screening using PAP test in Po Ly Ngai commune, Hoang Su Phi district, Ha Giang province in 2024. Subject and method: A cross-sectional descriptive study included 83 married and sexually active women aged 18 years and older who agreed to participate in the study in the voluntary medical examination program of the Faculty of Medicine, Dai Nam University in 2024. Results: Examination showed that the rate of cervical inflammation was high at 18.07%, followed by inflammation and vaginal yeast infection at 14.29%, vulvitis at 4.81% and cervical polyps at 2.41%. The results of cervical cytology showed a high rate of inflammation (48.19%), of which non-specific inflammation accounted for the majority at 87,5%, specific inflammation at 12.5%, mainly concentrated in the age group ≥ 55; dysplasia and low ASC accounted for 2-7%. Conclusion: The results of cervical cancer screening in Po Ly Ngai commune, Hoang Su Phi district, Ha Giang province in 2024 showed that the rate of women with cervicitis - vaginitis was high at 48.19%; low-grade dysplasia (7.23%), ASC was 2 cases (2.41%). These cases need regular check-ups, diagnostic biopsy, treatment and monitoring.